Towards a Legal and Regulatory Framework for South African Domestic Remittances: Some Considerations - Lawack, Vivienne (African Human Mobility Review, 2021)
This paper is an exploratory study that examines the legal and regulatory framework for domestic remittances within the South African legal context. The author makes some proposals for consideration in the review of the National Payment System Act No 78 of 1998 (NPS Act) with regards to domestic remittances as a retail, lowvalue payment service. To this end, the paper provides an understanding of domestic remittances, the transaction, process and channels used. It also contextualizes domestic remittances within the South African National Payment System (NPS) and finally examines the current gaps that can be remedied through the review of the NPS Act. The author argues that if financial inclusion is to be promoted, the regulatory framework pertaining to domestic remittances should enable, rather than inhibit the use of domestic remittances as a payment service.